2013
DOI: 10.1093/hmg/ddt132
|View full text |Cite
|
Sign up to set email alerts
|

TRAP1 rescues PINK1 loss-of-function phenotypes

Abstract: PTEN-induced kinase 1 (PINK1) is a serine/threonine kinase that is localized to mitochondria. It protects cells from oxidative stress by suppressing mitochondrial cytochrome c release, thereby preventing cell death. Mutations in Pink1 cause early-onset Parkinson's disease (PD). Consistently, mitochondrial function is impaired in Pink1-linked PD patients and model systems. Previously, in vitro analysis implied that the protective effects of PINK1 depend on phosphorylation of the downstream factor, TNF receptor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 68 publications
4
68
0
Order By: Relevance
“…Recently published studies have also indicated a similar role of TRAP1 in regulating stress resistance in flies (Costa et al, 2013, Zhang et al, 2013). However, we further demonstrate that dosage modulation of TRAP1 has remarkable sex-specific influences and is correlated with the sex-specific activation the UPR mt .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Recently published studies have also indicated a similar role of TRAP1 in regulating stress resistance in flies (Costa et al, 2013, Zhang et al, 2013). However, we further demonstrate that dosage modulation of TRAP1 has remarkable sex-specific influences and is correlated with the sex-specific activation the UPR mt .…”
Section: Discussionmentioning
confidence: 75%
“…TRAP1 also ameliorates cellular toxicity induced by α-synuclein in dopaminergic neurons (Butler et al . 2012) and expression of TRAP1 was able to rescue mitochondrial dysfunction in Pink1 deficient flies (Zhang et al , 2013; Costa et al , 2013). In summary, TRAP1 lies at an exciting intersection between ROS, aging, mitochondrial proteostasis and human disease.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, however, Zhang et al reported that overexpression of human TRAP1 was able to mitigate PINK1 but not PARKIN loss-offunction phenotypes in Drosophila. In human neuronal SH-SY5Y cells, TRAP1 also rescued mitochondrial fragmentation and dysfunction after siRNA-induced silencing of PINK1 but not PARKIN (Zhang et al 2013). This discrepancy in the relationships between PARKIN and TRAP1 remains poorly understood.…”
Section: Neurodegenerative Disorders: Pdmentioning
confidence: 93%
“…For example TRAP1 was identified in such a screen (Butler et al, 2012). TRAP1 is a mitochondrial chaperone that already had been implicated to be phosphorylated by another PD-protein Pink1 (Costa et al, 2013;Pridgeon et al, 2007;Zhang et al, 2013). Hence, such interaction screens start to elucidate common pathways that span several of the PD-relevant genes.…”
Section: Pd Modelling In Fliesmentioning
confidence: 99%
“…For example GST or removing Aconitase, a major mediator of ROS-induced toxicity in mitochondria are protective Kim and Yim, 2013;Whitworth et al, 2005). In addition, expression of Ret, TNF receptor-associated protein 1 (TRAP1) and near-infrared 808 nm light all turned out to improve mitochondrial function in Drosophila pink1 mutants thereby rescuing the cellular and behavioral defects in these animals Vos et al, 2013;Zhang et al, 2013). These strategies are thus paving the way to a new generation of therapeutic strategies in Pink1-dependent strategies.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%